2014
DOI: 10.1128/jvi.03014-13
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Recombination Hot Spots in the HIV-1 Genome

Abstract: HIV-1 infection is characterized by the rapid generation of genetic diversity that facilitates viral escape from immune selection and antiretroviral therapy. Despite recombination's crucial role in viral diversity and evolution, little is known about the genomic factors that influence recombination between highly similar genomes. In this study, we use a minimally modified fulllength HIV-1 genome and high-throughput sequence analysis to study recombination in gag and pol in T cells. We find that recombination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 69 publications
4
36
0
Order By: Relevance
“…This hotspot has previously been reported in a study on HIV-1 subtype B 72 . The hotspot positions II and IV have also been reported previously 73 . To date, eighteen distinct subtype G-related CRFs have been described (www.hiv.lanl.gov).…”
Section: Discussionsupporting
confidence: 77%
“…This hotspot has previously been reported in a study on HIV-1 subtype B 72 . The hotspot positions II and IV have also been reported previously 73 . To date, eighteen distinct subtype G-related CRFs have been described (www.hiv.lanl.gov).…”
Section: Discussionsupporting
confidence: 77%
“…We have recently shown that the rate of template switching varies across the HIV genome [31], and thus a gene-specific switching rate may be more appropriate. Owing to the limited availability of sequence data, it was not possible for us neither to compare the template-switching rate in this region with a rate in other regions nor to calculate the presence of recombination 'hotspots' over the env region.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are at least 98 CRFs , and numerous URFs identified, composed of pure and other recombinant subtypes including under‐sampled parental lineages that cannot be reasonably classified within the established HIV‐1 M subtypes . Recombination‐prone sites have been identified ; however, recombination events are scattered along the whole HIV genome . Most genotypic HIV‐1 M data is determined through partial genomic sequencing of one or a few limited regions.…”
Section: Introductionmentioning
confidence: 99%